1989
DOI: 10.1088/0268-1242/4/5/013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a peak in the temperature profile of the diffusion furnace for silicon solar cell fabrication

Abstract: A peak in the temperature profile has always been observed at the loading end of an air-cooled resistive heating diffusion furnace and it seems to be an inherent character of such furnaces. The shape of this peak under different setting conditions and its effect on t h e diffusion of impurities such as phosphorus and aluminium into silicon wafers for solar cell fabrication has been investigated. A difference upto 26 mV in the open circuit voltage has been observed because of this peak in the temperature profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This demands extreme care in maintaining a uniform temperature profile inside the diffusion furnace for consistent results. However, some authors observed that such furnaces have an inherent character such that their temperature profiles show a turbulent character at the loading zone of the furnace that could seriously affect the diffusion profile during the process [15].…”
Section: Emitter Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…This demands extreme care in maintaining a uniform temperature profile inside the diffusion furnace for consistent results. However, some authors observed that such furnaces have an inherent character such that their temperature profiles show a turbulent character at the loading zone of the furnace that could seriously affect the diffusion profile during the process [15].…”
Section: Emitter Formationmentioning
confidence: 99%
“…This makes the material particularly useful for critical applications which require minimum sensitivity tõ DOI 10.1007s12633-016-9458-0 thermal changes. Also, we expect the process to be cleaner in a POCl 3 furnace because of the use of quartz boats [15].…”
Section: Introductionmentioning
confidence: 99%